Responses to extreme drought in wintering waterbirds: a multi-species approach - Chenxi Wang; Shaoxia Xia; Xiubo Yu; Li Wen (Frontiers in Zoology, 2025)
Abstract Background Climate change and anthropogenic activities are accelerating environmental changes, challenging wild animals’ survival. Behavioral plasticity, such as adjusting habitat selection and foraging activity, is a key mechanism for responding to rapid environmental changes in the Anthropocene era. However, this shift may expose animals to new challenges. Moreover, not all behavioral plasticity is adaptive, as evidenced by ecological traps. This study focuses on Poyang Lake, a Ramsar wetland and a critical wintering ground for waterbirds in the East Asian–Australasian Flyway. Historically, the migratory patterns of waterbirds were synchronized with the plant life cycle. However, recent hydrological regime changes have diminished suitable habitats and food resources, thereby posing significant conservation challenges for waterbirds. Methods Utilizing multiyear satellite tracking data, we examined the variations in wintering home range and behaviors of four herbivorous waterbird species between natural and artificial wetlands in Poyang Lake under different hydrological conditions. Results Our results reveal significant differences in home range area and movement speed among species and across hydrological years. All species demonstrated a marked increase in their use of artificial wetlands under unfavorable conditions. Specifically, the Greater White-fronted Goose (Anser albifrons) shifted its distribution to artificial wetlands during drought years while favoring natural wetlands under normal conditions, indicating a stress-induced adaptation. In contrast, the Bean Goose (A. fabalis) and Swan Goose (A. cygnoid) displayed greater behavioral plasticity. Notably, the Siberian Crane (Leucogeranus leucogeranus) increasingly used artificial wetlands, likely due to human protection, raising concerns about potential ecological traps. Additionally, waterbirds foraging in artificial wetlands generally exhibited higher movement speeds during drought conditions. This behavior suggests maladaptation and a more dispersed distribution. Conclusions Our study underscored the critical role of artificial wetlands in supporting migratory waterbirds during drought, though elevated movement speeds observed in these habitats suggest potential maladaptation. Species-specific responses raise concerns about ecological traps if these habitats fail to meet key ecological needs. To ensure long-term conservation, efforts should focus on preserving natural wetlands and enhancing the quality of artificial habitats. Future research should prioritize long-term monitoring to guide habitat management and address species-specific needs in the face of climate change and habitat degradation. Graphic abstract